Climate Drives Modeled Forest Carbon Cycling Resistance and Resilience in the Upper Great Lakes Region, USA. Issue 1 (13th January 2022) - Dorheim, Kalyn; Gough, Christopher M.; Haber, Lisa T.; Mathes, Kayla C.; Shiklomanov, Alexey N.; Bond‐Lamberty, Ben
Abstract: Forests dominate the global terrestrial carbon budget, but their ability to continue doing so in the face of a changing climate is uncertain. A key uncertainty is how forests will respond to (resistance) and recover from (resilience) rising levels of disturbance of varying intensities. This knowledge gap can optimally be addressed by integrating manipulative field experiments with ecophysiological modeling. We used the Ecosystem Demography‐2.2 (ED‐2.2) model to project carbon fluxes for a northern temperate deciduous forest subjected to a real‐world disturbance severity manipulation experiment. ED‐2.2 was run for 150 years, starting from near bare ground in 1900 (approximating the clear‐cut conditions at the time), and subjected to three disturbance treatments under an ensemble of climate conditions. Both disturbance severity and climate strongly affected carbon fluxes such as gross primary production (GPP), and interacted with one another. We then calculated resistance and resilience, two dimensions of ecosystem stability. Modeled GPP exhibited a two‐fold decrease in mean resistance across disturbance severities of 45%, 65%, and 85% mortality; conversely, resilience increased by a factor of two with increasing disturbance severity. This pattern held for net primary production and net ecosystem production, indicating a trade‐off in which greater initial declines were followed by faster recovery. Notably, however, heterotrophic respiration responded more slowly to disturbance, and it's highly variable response was affected by different drivers. This work provides insight into how future conditions might affect the functional stability of mature forests in this region under ongoing climate change and changing disturbance regimes. Plain Language Summary: Forests play an important role in the carbon cycle. How forests respond and recover to disturbances is largely uncertain. Here, we use a model to investigate the effects of disturbances under different climatic conditions. Key Points: Climatic conditions affect how forests will respond to and recover from disturbances Disturbance severity strongly affects carbon fluxes